2008
DOI: 10.2967/jnumed.108.056085
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Gated Blood-Pool SPECT Regional Left Ventricular Function Measurements

Abstract: Blood-pool (BP)-gated SPECT should be able to detect regional left ventricular (LV) dysfunction, as the modality is fully 3-dimensional and capable of resolving all cardiac chambers. This study investigates the hypothesis that LV segments that have abnormal regional wall motion (WM) on a cardiac MRI scan also have abnormal BP regional ejection fraction (EF) as computed by fully automated quantitation (AQ) of BP data. Methods: A total of 34 patients evaluated for coronary artery disease who underwent visual ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
2
20
0
3
Order By: Relevance
“…On the other hand, in the presence of perfusion defect, in higher SRS scores and in patients with larger ventricle (ESV ≥ 25 ml), no remarkable difference was noticed between two modalities. Similarly to our study, previous studies that compared GSPECT and ECHO, reported good agreement between LVEF, EDV and ESV values [2,9,[12][13][14][15][16][17]. Zanger et al [18] reported a good agreement between ECHO and GSPECT for determination of LVEF and LVVs.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, in the presence of perfusion defect, in higher SRS scores and in patients with larger ventricle (ESV ≥ 25 ml), no remarkable difference was noticed between two modalities. Similarly to our study, previous studies that compared GSPECT and ECHO, reported good agreement between LVEF, EDV and ESV values [2,9,[12][13][14][15][16][17]. Zanger et al [18] reported a good agreement between ECHO and GSPECT for determination of LVEF and LVVs.…”
Section: Discussionsupporting
confidence: 70%
“…21 A study similar to ours, comparing LVEF by Tc-99 m-sestamibi and the 2-DE method of disc measurement in 201 community-based patients, obtained almost identical results. 22 One may argue that visual eyeball estimation of LVEF by 2-DE is inaccurate, and that direct measurements using published techniques such as the area-length method or the biplane method of discs (modified Simpson's rule) 13 are more reliable. However, eyeball estimation competency and its validity, especially when performed by experienced echocardiologists, are well established.…”
Section: -Dementioning
confidence: 99%
“…Subsequent studies compared the QGS results with other reference techniques, such as equilibrium radionuclide angiocardiography (ERNA), echocardiography, contrast ventriculography and magnetic resonance imaging [16, 19-21, 23, 26-36, 55]. The Emory Cardiac Toolbox (ECTb, Emory University, Atlanta, GA) has also been extensively validated by comparison with first-pass radionuclide ventriculography, ERNA, echocardiography and magnetic resonance imaging [23,25,30,34,55]. Furthermore, comparative studies with ERNA and magnetic resonance imaging have confirmed the reliability of 4D-MSPECT (University of Michigan Medical Center, Ann Arbor, MI) [32,34,55,56].…”
Section: Value Of Gated Spect For Estimating Left Ventricular Functionmentioning
confidence: 99%